Ambiguity at the peri-urban interface in Australia. (November 2018) - Amirinejad, Ghazal; Donehue, Paul; Baker, Douglas
Highlights: Ambiguity and uncertainty recognition in the peri-urbanisation processes. Ambiguity of definition and naming. Ambiguity of characteristics. Ambiguity of typologies. Ambiguity in terms of policy-making and implementation. Abstract: Peri-urban areas display the common trait of ambiguity, in spite their considerable variety in terms of origins, definitions, and extent. Rather than the traditional dichotomy of rural and urban that forms much of the traditional view of this aspect of the built environment, there is a complex set of land use relationships that exist, creating the fluid phenomenon of peri-urbanisation. Ambiguity is an inseparable and inevitable characteristic of the peri-urban interface with a wide variety of manifestations. This paper, set in the context of Australia, argues that it is important to understand the nature of this ambiguity in order to make informed policy decisions within the context of the peri-urban interface. In particular, it identifies specific categories of peri-urban ambiguities; those relating to definition, characteristics, typology, and policy making and implementation.